(untitled) (International Journal of Medical and Surgical Sciences, 2015)
MicroRNAs (miRNAs) are a class of small RNA molecules noncoding to proteins, which regulate gene expression at post-transcriptional level by binding to specific sequences within target genes. miRNAs have been recognized as important regulatory factors in the body development and expression of certain diseases. Some miRNAs regulate the proliferation and differentiation of cells and tissues during odontogenesis.